Increased natural killer cell activity in viremic HIV-1 infection - Alter, Galit; Malenfant, Jessica M; Delabre, Rosemary M; Burgett, Nicole C; Yu, Xu G; Lichterfeld, Mathias; Zaunders, John; Altfeld, Marcus (The Journal of immunology (1950), 2004)
NK cells are a subset of granular lymphocytes that are critical in the innate immune response to infection. These cells are capable of killing infected cells and secreting integral cytokines and chemokines. The role that this subset of cytolytic cells plays in HIV infection is not well understood. In this study, we dissected the function of NK cells in viremic and aviremic HIV-1-infected subjects, as well as HIV-1-negative control individuals. Despite reduced NK cell numbers in subjects with ongoing viral replication, these cells were significantly more active in secreting both IFN-gamma and TNF-alpha than NK cells from aviremic subjects or HIV-1-negative controls. In addition, NK cells in subjects with detectable viral loads expressed significantly higher levels of CD107a, a marker of lysosomal granule exocytosis. The expression of CD107a correlated with NK cell-mediated cytokine secretion and cytolytic activity as well as with the level of viral replication, suggesting that CD107a represents a good marker for the functional activity of NK cells. Finally, killer Ig-related receptor+ NK cells were stable or elevated in viremic subjects, while the numbers of CD3-/CD56+/CD94+ and CD3-/CD56+/CD161+ NK cells were reduced. Taken together, these data demonstrate that viremic HIV-1 infection is associated with a reduction in NK cell numbers and a perturbation of NK cell subsets, but increased overall NK cell activity.